2002
DOI: 10.1128/jvi.76.22.11710-11714.2002
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Tumor Necrosis Factor Alpha (TNF-α) in Human Immunodeficiency Virus Type 1-Transgenic Mice: Prevention of Death by Antibody to TNF-α

Abstract: Homozygous human immunodeficiency virus type 1 (HIV-1)-transgenic mice (Tg26) appear normal at birth but die within 3 to 4 weeks. The skin of these animals shows diffuse scaling and high-level expression of both HIV-1 mRNA and gp120. Previous experiments showed that treatment with human chorionic gonadatropin (hCG) prevented death and the expression of HIV-1 mRNA and gp120. The present experiments were initiated to study the role of tumor necrosis factor alpha (TNF-␣) in HIV-1-induced pathology. Examination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…In one such study, TNF-α was observed to be constitutively expressed in 62 HIV infected individuals (24). This may account for the decline in the absolute CD4 + T cell counts as TNF-α augments this decline by T cell dependent ADCC (25). In the present study, we have observed the significant rise of TNF-α mRNA expression once the children between 1-5 years presented with HIV-associated opportunistic infections.…”
Section: Discussionsupporting
confidence: 58%
“…In one such study, TNF-α was observed to be constitutively expressed in 62 HIV infected individuals (24). This may account for the decline in the absolute CD4 + T cell counts as TNF-α augments this decline by T cell dependent ADCC (25). In the present study, we have observed the significant rise of TNF-α mRNA expression once the children between 1-5 years presented with HIV-associated opportunistic infections.…”
Section: Discussionsupporting
confidence: 58%
“…Another study showed that treatment with hCG prevented the wasting and death of transgenic mice carrying human immunodeficiency virus genes [7]. Recent studies have shown that this wasting syndrome is due in part to high levels of TNF-α, which can be suppressed by treatment with hCG [8]. However, the mechanisms by which hCG prevents autoimmune disease are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The studies reported here extend previous findings that showed TM enhanced the pathogenicity of Semliki Forest virus and encephalomyocarditis virus in mice. 19 Taken together, these studies indicate that TM should be included in the growing list of agents reported to enhance viral neuroinvasion, which already includes lipopolysaccharide, 18 TNF-a, 5 the dengue virus-induced cytokine called cytotoxic factor, 3 acetylcholinesterase inhibitors, 10 and cocaine. The exact mechanism by which TM enhanced neuroinvasion by VEE viruses is not clear from these studies.…”
Section: Discussionmentioning
confidence: 99%